Following Trends or Adapting: Conformity and Consumer Behavior in the Purchase of Beauty Products Among Female Students at Mulawarman University - Jessica Cika; Ridha Wahyuni (Psikologi Prima, 2026)
The growing trend of beauty product use among female college students indicates a shift in purchasing behavior influenced by social factors. The purpose of this study is to examine the relationship between conformity and consumer behavior in the purchase of beauty products among female students at Mulawarman University. This study employs a quantitative approach with a correlational design. The number of participants in this study, calculated using G*Power 3.1, was 115 female students selected through purposive sampling. Data were collected using a Likert scale to measure conformity and consumer behavior. Pearson’s product-moment correlation was then used to analyze the data after testing for normality and linearity. The results of the study indicate a correlation between conformity and consumerist behavior of r = 0.492; p = 0.000, showing that the two variables are positively and significantly correlated. This means that the higher the level of conformity, the greater the tendency toward consumerist behavior, so that purchasing decisions are not entirely based on need. This study is expected to provide insight into the influence of the social environment on the consumption behavior of female students at Mulawarman University regarding the purchase of beauty products.